Analysis of a spring 2013 Antarctic ozone hole pass over Río Gallegos, Argentina - Laino Baldini, Cristian Ariel (2023)
During springtime, subpolar regions in the Southern Hemisphere are influenced by the Antarctic ozone hole (AOH), leading to variations in total ozone column (TOC) at different latitudes. This phenomenon impacts on the ultraviolet (UV) solar radiation reaching Earth's surface. This work focuses on a specific case study at Río Gallegos, Argentina (51.5 °S, 69.3 °W; 15 m a. s. l.), during the period from September to November 2013 when the AOH passed over the region. TOC measurements from satellite data obtained from OMI and a ground-based SAOZ instrument were analyzed, and climatological TOC was calculated. On the specific date of October 16, 2013, a TOC value of 178.5 DU was found, while the climatology of the TOC calculated for that day was equal to 325.9 DU. On the day of the observed TOC decrease, the UVI was measured with ground-based Multi Band Filter Radiometer GUV541 and it was also calculated under clear sky conditions using a parametric model adapted for Río Gallegos to analyze the impact of the ozone hole on the surface UV radiation. Subsequently, the erythemal daily doses of UV radiation was retrieved. We estimate an erythemal daily dose under clear sky conditions of 5.6 kJ/m², which represents an increase greater than 100% with respect to the climatology (2.7 kJ/m²). The measurement reflected values below the climatology due the strong attenuation by clouds.